Understanding Intercultural Competence and its Assessment Tools - Islom Boynazarov (Genius Publishing Group, 2022)
New technology and information systems, migration and the growing internationalisation of many economic sectors are some of the issues that nowadays put us into contact with people whose cultural background is different from our own. People at work need to be able to communicate in this ‘new world’ of diverse colleagues, clients and customers. Numerous people have to work in multicultural teams or engage in cross border negotiations or execute projects in foreign countries. Students therefore more and more need to develop competencies to operate in an intercultural context. This not only asks for education programs that respond to this need, but it is also necessary to formulate the components of this intercultural competence and develop assessment methods to measure it
Keywords: New technology; information systems; intercultural